THE ANTIBACTERIAL EFFECTS OF ESSENTIAL OIL FROM GALANGAL RHIZOME Alpinia galanga (Linn.) Pierre ON RAT (Rattus norvegicus L.) WERE INFECTED BY Salmonella typhi - Eff, Aprilita Rina Yanti; Rahayu, Sri Teguh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
The research was conducted to evaluate the antibacterial effect ofÂ essential oils galangal rhizome on rat were infected by Salmonella typhi. This study begins by isolating the essential oils galangal rhizome (Alpinia galanga (Linn.) Pierre.) followed by tested the antibacterial activity of Salmonella typhi in rats (Rattus norvegicus L.) using the Widal test for measuring antibody titre of Salmonella antigen. Mice were divided into six treatment groups, ie normal control group (NoCG),Â Â negative control group (NCG) given PGA 10%, positive control group (PCG)Â given the suspension of chloramphenicol 8 mg/250 g BW, experimental group 1 (EG1) given the emulsion of essential oil at the doseÂ 25 mg / ml, experimental group 2 (EG2) given the emulsion of essential oil at the dose 50 mg / ml, and the experimental group 3 (EG3) given the emulsion of essential oil at the dose 75 mg / ml. Â Before treated, mice were adapted for 2 weeks and measurement of antibody titre (Widal test 1) as a baseline, then the mice induced by Salmonella typhi suspension oral.Â OnÂ day 8 titre antibody was measuringÂ and followed the administration of the test material orally 3 times a day for 7 consecutive days - respectively. On day 14 measurements of antibody titre was repeated (Widal 3) to see the effectiveness of treatment. Results show that essential oil from Galangal (Alpinia galanga (Linn.) Pierre.) at the dose 25mg/ml, 50 mg/ml and 75 mg/ml can reduce antibody titre of Salmonella antigen. Â Keywords: antibacterial effects, essential oil, galangal rhizome, Salmonella typhi, Widal test